Factors effecting menopausal age - ES Hajikazemi (نشریه پرستاری ایران, 1999)
Background: Factors effecting menopausal age are many, including body mass index (8M!), menstural and reproductive history. Objective: To determine the relation between 8MI, menstural and reproductive factors and menopausal age . Design: It was a correlational study. The data was drawn from one group of women. Variables were correlated using proper statistical tests. Sample: Three hundred menopausic women were chosen by cluster random sampling. The study was conducted in north of Tehran. Result: Findings indicated that menopausal age was posetively related to 8MI, duration of menstural cycle, and number of pregnancies. The age of first pregnancy had an inverse effcet. Conclusion: The age of first pregnancy is an important factor that needs special attention and program planning.